ASSESSMENT OF EPIDEMIOLOGICAL TRENDS AND THE EFFECTIVENESS OF PREVENTIVE MEASURES AGAINST MEASLES AMONG CHILDREN - Samadaliyev N. N. (Web of Journals Publishing, 2025)
Measles is one of the most highly contagious viral infectious diseases among children. In recent years, factors such as declining vaccination coverage, migratory movements, inadequate performance of epidemiological surveillance systems, and disruptions in healthcare services following the pandemic have contributed to the resurgence of this disease. This scientific article analyzes the epidemiological dynamics of measles incidence among children, including risk factors, age-specific distribution, and regional characteristics. Furthermore, the effectiveness of vaccination strategies, the impact of supplementary immunization activities, and the role of herd immunity in disease prevention are evaluated. The analysis is based on national and global statistical data, revealing the interrelation between the coverage level of preventive measures and the spread of the disease. The study concludes with practical recommendations aimed at strengthening epidemiological control, optimizing immunization approaches, and implementing comprehensive preventive interventions.
Keywords: Measles, child health, epidemiological analysis, vaccination, prevention, herd immunity, public health, immunization coverage, epidemiological surveillance, supplementary immunization.